2021
DOI: 10.3390/electronics10020208
|View full text |Cite
|
Sign up to set email alerts
|

Latencies in Power Systems: A Database-Based Time-Delay Compensation for Memory Controllers

Abstract: Time-delay is inherent to communications schemes in power systems, and in a closed loop strategy the presence of latencies increases inter-area oscillations and security problems in tie-lines. Recently, Wide Area Measurement Systems (WAMS) have been introduced to improve observability and overcome slow-rate communications from traditional Supervisory Control and Data Acquisition (SCADA). However, there is a need for tackling time-delays in control strategies based in WAMS. For this purpose, this paper proposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Normally, communication delays can range from several microseconds to hundreds of milliseconds [40,75,88,89]. Moreover, according to some other reports [62,86], the normal 150 to 300 milliseconds of telecommunications are considered to be the plans to perform actual transient stability control system, stability index, fault clearance time and delay in response. In this work, a lot of simulation is done with different values of delay.…”
Section: Ieej West 10-machine Model System Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Normally, communication delays can range from several microseconds to hundreds of milliseconds [40,75,88,89]. Moreover, according to some other reports [62,86], the normal 150 to 300 milliseconds of telecommunications are considered to be the plans to perform actual transient stability control system, stability index, fault clearance time and delay in response. In this work, a lot of simulation is done with different values of delay.…”
Section: Ieej West 10-machine Model System Resultsmentioning
confidence: 99%
“…In reference [16,62], the authors discussed the effects of time-delays in WAMS-based monitoring activities on the performance of the system [63]. Molina-Cabrera A et al demonstrated the ETDC, which uses a delay method to differentiate a line delay method rather than a deadline; moreover, the ETDC uses real-time signals and how to send measurements to WAMS that builds a closed-loop database system [62].…”
Section: Previous and Current Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Two papers discuss the issues related to the time framework. In article [2], the enhanced time delay compensator approach manages varying time delays inherent to communications schemes in power systems. This introduces the perspective of network latency instead of dead time.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%